THE IMPLEMENTATION OF COMMUNICATIVE LANGUAGE TEACHING IN TEACHING ENGLISH TO THE FIFTH YEAR STUDENTS OF SDN PELEMAN II GEMOLONG SRAGEN IN 2010/2011 ACADEMIC YEAR - RISPATININGSIH, DWI MARYANI (2011)
This research paper aims to analyze the implementation of communicative Language Teaching in teaching English to the fifth year students of SDN Peleman 2 Gemolong Sragen in 2010/2011 academic year. This research is Classroom Action Research. The goal of teaching English at SDN Peleman 2 Gemolong Sragen is that the students are able to communicate using English. The objective of this research paper is to describe the design, classroom procedure and discussion of finding for teaching learning of English at SDN Peleman 2 Gemolong Sragen. The reseach paper focuses on the teaching learning process. The result of the analysis shows that the process of teaching learning process using CLT is a suitable method for teaching English, but the implementation in teaching learning process at SD Peleman 2 Gemolong Sragen is not yet perfect. The effectiveness in teaching learning process at SDN Peleman 2 Gemolong Sragen can be seen in the following activities, such as: the students are able to express their own ideas; they were active and communicative in teaching learning process; they get direct experience to use English language as communication, and between the teacher and the students have interaction in teaching learning process. The ineffectiveness in teaching learning process at SD Peleman 2 Gemolong Sragen is that the teacher does not use the English language as communication every time, because the students still have poor vocabulary.